PENYISIHAN BAKTERI E. COLI MENGGUNAKAN RADIASI SINAR ULTRAVIOLET DAN SEMIKONDUKTOR TIO2 PADA AIR SUMUR DESA KENONGO, SIDOARJO - Yayok Suryo Purnomo; Hendrikus Labina (EnviroUS, 2022)
There are many sources of water on earth, and they are divided into 4 types, namely sea water or salt water, atmospheric water or rain water, surface water including rivers, lakes, swamps, and other bodies of water. Lastly, there is groundwater. Well water contaminated with pathogenic bacteria shown by E. coli makes well water undrinkable as clean drinking water. Escherichia coli is a bacterium that indicates contamination of clean water. This study aims to design a tool to eliminate E. coli so that the well water of the people of Porong, Sidoarjo Regency can meet their daily needs. The photolysis process with changes in the diameter of the reactor, namely 2.5", 3" and 4', and exposure times of 5, 10, 15, 20 and 25 minutes, will be used to exclude E. The photolysis process in this reactor uses a 20 watt UV lamp, = 253.7 nm. Analysis of the data used is to eliminate the correlation between Escherichia coli with the photolysis process and the combination of reactor changes. After being exposed to the 2.5-inch reactor for 25 minutes, the E. coli removal rate was up to 86%. At the same time, during the photolysis process, reactor 3 was exposed for 25 minutes, and the E. coli removal rate reached 83%. And the exposure time in the 4" reactor is 25 minutes, and the E. coli removal rate reaches 81%